Deracemization in a Complex Quaternary System with a Second‐Order Asymmetric Transformation by Using Phase Diagram Studies. Issue 61 (20th September 2019) - Oketani, Ryusei; Marin, Francesco; Tinnemans, Paul; Hoquante, Marine; Laurent, Anne; Brandel, Clément; Cardinael, Pascal; Meekes, Hugo; Vlieg, Elias; Geerts, Yves; Coquerel, Gérard
Abstract: Invited for the cover of this issue is the group of Gérard Coquerel at Université de Rouen Normandie. The image depicts a pyramid‐like tetrahedron of the quaternary phase diagram showing where symmetry breaking can take place. Read the full text of the article at 10.1002/chem.201903338 . Abstract : " In our daily life, map apps are essential for many people to access their destinations. Phase diagrams play a similar role to map apps in the crystallization ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 13890 ff. (DOI: 10.1002/chem.201903338 ).